STRATEGI ADAPTASI MAHASISWA YANG MEMPEROLEH BEASISWA BELAJAR DI JEPANG DALAM MENGHADAPI GEGAR BUDAYA (Studi Kasus Enam Mahasiswa Program Studi Bahasa Dan Sastra Jepang Fakultas Ilmu Budaya Universitas Gadjah Mada) - , THIWUK JATININGTYAS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This paper, describe about adaptation strategy of UGM language and literature students who got scholarships to Japan. This research is focused on 6 students who studied in Japan for 1 year by Japanese governmentâs scholarships from 2010 until 2012. There are three theory that used in this paper. The first theory in this paper is intercultural communication theory to explain about communication between Indonesian students and Japanese society. The second theory is culture shocks theory from Kalvero Oberg is needed to analyze the existence of culture differences in communication which cause culture shocks. The last theory which is used in this research is adaptation theory. Which is used for explaining the adaptation strategy that Indonesian students do in facing shocks culture. The research method used in this research is qualitative. The result of the research shows that culture shocks which are experienced in daily life in Japan are related to the language, behavior, customes, religy, technology, transportation, stereotype, food and season. Culture shocks do not only happen when people are in Japan, but also they will get re-entry shocks when they have been in Java. The adaptation strategy in facing the obstacles that occur because of the different culture used by each Indonesian student is different.